2021
DOI: 10.1111/ecin.13018
|View full text |Cite
|
Sign up to set email alerts
|

Trade openness and income inequality: New empirical evidence

Abstract: We examine how trade openness influences income inequality within countries. The sample includes 139 countries over the period 1970–2014. We employ predicted openness as instrument to deal with the endogeneity of trade openness. The effect of trade openness on income inequality differs across countries. Trade openness tends to disproportionately benefit the relative income shares of the very poor, but not necessarily all poor, in emerging and developing economies. In most advanced economies, trade openness inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 86 publications
6
44
1
2
Order By: Relevance
“…Although existing studies on the relationship between trade opening and income disparity found that trade opening reduces labor income share, thereby widening income disparity (Jayadev, 2007 ; Asteriou et al, 2014 ), these empirical analyses mainly focused on trade opening among developed economies, while this paper focuses on a developing country. Contrary to the conclusions of these studies, many studies suggested that when countries engage in trade opening, the production factors that are relatively abundant gain, especially in developing countries can gain a larger share of labor income through trade opening, which in turn leads to a decrease in income inequality (Jaumotte et al, 2013 ; Roser and Cuaresma, 2016 ; Khan et al, 2020 ; Dorn et al, 2022 ). These previous studies further provide empirical support for the rationality of the research hypothesis in this paper.…”
Section: Discussionmentioning
confidence: 88%
“…Although existing studies on the relationship between trade opening and income disparity found that trade opening reduces labor income share, thereby widening income disparity (Jayadev, 2007 ; Asteriou et al, 2014 ), these empirical analyses mainly focused on trade opening among developed economies, while this paper focuses on a developing country. Contrary to the conclusions of these studies, many studies suggested that when countries engage in trade opening, the production factors that are relatively abundant gain, especially in developing countries can gain a larger share of labor income through trade opening, which in turn leads to a decrease in income inequality (Jaumotte et al, 2013 ; Roser and Cuaresma, 2016 ; Khan et al, 2020 ; Dorn et al, 2022 ). These previous studies further provide empirical support for the rationality of the research hypothesis in this paper.…”
Section: Discussionmentioning
confidence: 88%
“…(3) Coordination Cost: This cost is mainly the communication and coordination cost during the implementation of the contract. In the process of enterprise projects, due to the diversity of market demand and the variability of the future, the contracts signed between enterprises will be affected by many factors [13], which will lead to accidents in the process of cooperation. Therefore, enterprises need to coordinate accordingly and renegotiate the contents of the contracts to generate new transaction costs, which constitute coordination costs.…”
Section: The Accounting Audit Transaction Cost Analysismentioning
confidence: 99%
“…If one has an adequate understanding of economic protectionism, this should-as a mirror view of protectionism-also lead to a more refined understanding of sustained economic liberalization; that is, an economic globalization that can be expected to be rather stable. This naturally leads to a consideration of certain aspects of economic liberalization which cannot be covered here, but the analysis presented could be picked up in the ongoing debate by using CES production functions and inequality aspects in the modeling of the supply side; for contributions to the traditional, and more recent, debate see, for example, Jaumotte et al (2008) and Dorn et al (2021).…”
Section: Further Research and Policy Conclusionmentioning
confidence: 99%